2020
DOI: 10.1093/jhered/esaa024
|View full text |Cite
|
Sign up to set email alerts
|

New Genetic Insights About Hybridization and Population Structure of Hawksbill and Loggerhead Turtles From Brazil

Abstract: An extremely high incidence of hybridization among sea turtles is found along the Brazilian coast. To understand this atypical phenomenon and its impact on sea turtle conservation, research focused in the evolutionary history of sea turtles is fundamental. We assessed high quality multilocus haplotypes of 143 samples of the five species of sea turtles that occur along the Brazilian coast to investigate the hybridization process and the population structure of hawksbill (Eretmochelys imbricata) and loggerhead t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 89 publications
1
23
0
Order By: Relevance
“…Previous investigations of current hybridization patterns from Brazil have failed to detect backcross hybrids beyond F2s between hawksbills, loggerheads, and olive ridleys (Arantes et al, 2020 ; Vilaça et al, 2012 ). Our results show hybridization within Carettini after species divergence, and since these events can still be detected in genome‐wide markers, backcrossing must have happened in the past.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations of current hybridization patterns from Brazil have failed to detect backcross hybrids beyond F2s between hawksbills, loggerheads, and olive ridleys (Arantes et al, 2020 ; Vilaça et al, 2012 ). Our results show hybridization within Carettini after species divergence, and since these events can still be detected in genome‐wide markers, backcrossing must have happened in the past.…”
Section: Discussionmentioning
confidence: 99%
“…F1 hybrids can backcross with both parental species and produce viable offspring (Soares et al, 2017 , 2018 ), supporting the idea that the genome mixing that occurs today may have long term consequences. However, later generation hybrids among adult individuals have not been found yet (Arantes et al, 2020 ), and it is not known how frequently hybridization may have occurred in the sea turtles’ evolutionary past.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related species are known to be more prone to hybridization (Abbott et al, 2013), and although introgression between distant taxa has been reported previously (e.g., Arantes et al, 2020; Zhang et al, 2016), it is less common in nature than gene flow between close relatives. Here we examine a case of gene flow between two distantly related species of the genus Melitaea (Lepidoptera, Nymphalidae).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids were found to migrate to foraging areas typical of both parental species (Marcovaldi et al, 2010(Marcovaldi et al, , 2012. However, the relationship between the hybrids' genetic composition and their migratory pattern is not clear since a combination of mtDNA sequences (Lara-Ruiz et al, 2006) and few nuclear loci identified them as first generation (F1) (Arantes, Vilaça, Mazzoni, & Santos, 2020;Vilaça et al, 2012). The limits of these studies concern both the use of mtDNA and the number of nuclear loci.…”
Section: Introductionmentioning
confidence: 99%